The improvement of medical services as an essential component of changes to the medical care system - Marzena Furtak-Niczyporuk; Martyna Warchoł; Patrycja Gierszon; Iwona Firosz; Sylwia Mojsym-Korybska (Kazimierz Wielki University, 2018)
The high quality of the medical services, it's constant improvement and custom approach to the patients needs stand as one of the most important issues of modern healthcare. The patient, being beneficiary, shapes the market of health services through expressing his opinions and expectations. The exclusion of their feedback during management might lead to the loss of reputation on the medical services market. The term "quality", same as "health" is subjective. Defining quality will depend on experience, knowledge, demands, and expectations of the clients. The aim of the article is to survey the patients' opinions and expectations towards the quality of healthcare services. The patients expect the constant improvement of that quality during ongoing changes to the healthcare system. They place it very high on their priorities' list. To them quality equals security and medical professionalism. The nature of providing medical services entails that higher quality demand are not possible to meet without overall improvement of how the patients are taken care of.